The Effect Of Profesional Ethics, Time Budget Pressure, Professional Skepticsm On Audit Quality - Krisdayanti, Monica Indah; Andesto, Ronny; Praptiningsih, Praptiningsih (Jurnal Ilmiah Akuntansi Kesatuan, 2020)
This study aims to examine the effect of professional ethics, time budget pressure, professional skepticism on audit quality. The population in this study was auditors working at BPK Republic of Indonesia. Sampling was carried out using the puruposive method. The data analysis used in this study used the PLS program with a significance level of 5%. The results of this study indicate that (1) professional ethics has a significant effect on audit quality, (2) time budget pressure has no significant effect on audit quality, (3) professional skepticism has no significant effect on audit quality. Keywords: Professional Ethics; Time Budget Pressure; Professional Skepticism; Audit Quality